PERGESERAN SUDUT PANDANG PENGUJIAN PERATURAN KEBIJAKAN - Gede Marhaendra Wija Atmaja (Jurnal Komunikasi Hukum, 2022)
This research is a normative legal research that aimed to finding answers of the research problem, shifting the point of view on policy regulations review. The results of the study show that there is a shift in the point of view of policy regulations review, namely the point of view of policy regulations in the context of legislation shifts to the point of view of policy regulations not in the context of laws and regulations. The first point of view gives birth to the establishment of policy regulations as laws and regulations or not which leads to the acceptance or rejection of the review. The second point of view boils down to policy regulations that can be the object of review as "other powers granted by law".